Commodity prices and the dynamics of inflation in commodity-exporting nations: Evidence from Australia and Canada - Bloch, Harry; Dockery, Alfred Michael; Sapsford, D. (Blackwell Publishing Asia, 2006)
A commodity-price boom is under way. What does this boom mean for inflation in coutnries with substantial net commodity exports? The answer depends on movements in commodity prices, changes in foreign exchange rates and the determinants of domestic price inflation. We estimate equations to provide indications of the strength of each of these forces for both Australia and Canada. The results show that world commodity prices move pro-cyclically with world industrial production and that rates of change in commodity prices are directly related to domestic inflation in both countries. However, there is an offsetting impact of exchange-rate changes, which is strong enough in the case of Australia, but not Canada, to substantially eliminate the inflationary impact of a commodity-price boom.